Internationalization of Chinese Manufacturing SMEs - Wang, Beini (2017)
With the increased speed of market liberalization and digitization, internationalization has become a necessary strategy for firms’ development. Based on different kind of motivations, firms through exporting products, licensing or joint venture with local entities, establishing foreign sales subsidiary or direct foreign production to involve in international market. There are many previous researches studied the firm internationalization in different perspectives, however, most of them are based on large or well-established multinational enterprises. In recent years, small and medium enterprises have gradually become the main body of international business, which result in more and more scholars pay attention to the internationalization of SMEs. Different with developed Western countries, firms in emerging countries always be regarded to have specific characteristics. China is the largest emerging country, and the researches focus on Chinese market usually can provide some experience to other emerging countries. To fill the gap of internationalization research in SMEs in emerging countries, this paper uses Chinese manufacturing SMEs as sample and aims to find out the specific characteristics of Chinese market.